Outbreaking forest insect drives phase synchrony among sympatric folivores: Exploring potential mechanisms. Issue 4 (18th August 2020) - Liebhold, Andrew M.; Björkman, Christer; Roques, Alain; Bjørnstad, Ottar N.; Klapwijk, Maartje J.
Abstract: We explore a common feature of insect population dynamics, interspecific synchrony, which refers to synchrony in population dynamics among sympatric populations of different species. Such synchrony can arise via several possible mechanisms, including shared environmental effects and shared trophic interactions, but distinguishing the relative importance among different mechanisms can be challenging. We analyze interannual time series of population densities of the larch budmoth, Zeiraphera griseana (Lepidoptera: Tortricidae), along with six sympatric larch‐feeding folivores from a site in the European Alps 1952–1979. These species include five lepidopterans, Exapate duratella, Ptycholomoides aeriferana, Spilonota laricana, Epirrita autumnata and Teleiodes saltuum, and one hymenopteran sawfly Pristiphora laricis . We document that the highly regular oscillatory behavior (period 9–10 years) of Z . griseana populations is similarly evident in the dynamics of most of the sympatric folivores. We also find that all of the sympatric species are phase synchronized with Z . griseana populations with half of the sympatric species exhibiting nonlagged phase synchrony and three of the species exhibiting 2–5 year lags behind Z . griseana populations. We adapt a previously developed tritrophic model of Z . griseana dynamics to explore possible mechanisms responsible for observed phase synchronization. Results suggest that either shared stochastic influences (e.g., weather) or shared parasitoid impacts are likely causes of nonlagged phase synchronization. The model further indicates that observed patterns of lagged phase synchronization are most likely caused by either shared delayed induced host plant defenses or direct density‐dependent effects shared with Z . griseana . Abstract : Time series of the annual density of the larch budmoth from the European Alps were compared with those of six sympatric larch‐feeding folivores. All six species showed evidence of the same periodic behavior found in larch budmoth and were phase locked, either in phase with the larch budmoth or out of synch by 3 to 6 years. A tritrophic model was used to explore mechanisms responsible for observed interspecific synchrony and suggests that synchrony may arise either by top‐down or bottom‐up trophic interactions.